2015
DOI: 10.1111/jcmm.12551
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanism of cardiac protection by valsartan: synergetic roles of TGF‐β1 and HIF‐1α in Ang II‐mediated fibrosis after myocardial infarction

Abstract: Transforming growth factor (TGF)-β1 is a known factor in angiotensin II (Ang II)-mediated cardiac fibrosis after myocardial infarction (MI). Hypoxia inducible factor-1 (Hif-1α) was recently demonstrated to involve in the tissue fibrosis and influenced by Ang II. However, whether Hif-1α contributed to the Ang II-mediated cardiac fibrosis after MI, and whether interaction or synergetic roles between Hif-1α and TGF-β pathways existed in the process was unclear. In vitro, cardiac cells were incubated under hypoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 33 publications
(39 reference statements)
6
31
1
Order By: Relevance
“…It is well‐known that the TGF‐β1/Smad3 pathway is a central mediator in cardiac remodelling and exerts multiple biological effects, including cell proliferation, differentiation, apoptosis, autophagy and extracellular matrix production . A large body of evidence has demonstrated that TGF‐β1 is dramatically up‐regulated in the remodelling heart in both patient and animal experimental models, and has been used as a marker of cardiac remodelling .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well‐known that the TGF‐β1/Smad3 pathway is a central mediator in cardiac remodelling and exerts multiple biological effects, including cell proliferation, differentiation, apoptosis, autophagy and extracellular matrix production . A large body of evidence has demonstrated that TGF‐β1 is dramatically up‐regulated in the remodelling heart in both patient and animal experimental models, and has been used as a marker of cardiac remodelling .…”
Section: Discussionmentioning
confidence: 99%
“…It is well‐known that the TGF‐β1/Smad3 pathway is a central mediator in cardiac remodelling and exerts multiple biological effects, including cell proliferation, differentiation, apoptosis, autophagy and extracellular matrix production . A large body of evidence has demonstrated that TGF‐β1 is dramatically up‐regulated in the remodelling heart in both patient and animal experimental models, and has been used as a marker of cardiac remodelling . Moreover, the over‐expression of active TGF‐β1 in the rodent heart induces the fibrotic response, whereas down‐regulation of TGF‐β1 with a neutralizing antibody, antisense oligonucleotides, inhibitors, or genetic deletion of receptors attenuates cardiac remodelling in vivo and in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Transfecting hypoxic mouse fibroblasts with HIF‐1α siRNA ameliorates TGF‐β‐induced α‐SMA, a marker of pathologic fibroblast activity, and FGF expression in comparison with fibroblasts transfected with scrambled siRNA . HIF‐1α and TGF‐β play a synergistic role in myocardial fibrosis under hypoxic conditions . HIF‐1α and TGF‐β synergistically increase differentiation of endomyocardial fibroblasts into myofibroblasts that contribute to ECM synthesis .…”
Section: Adipose Tissue Fibrosis and Inflammationmentioning
confidence: 98%
“…Inflammation and resulting fibrosis are integral parts of the pathogenesis of diastolic dysfunction. HIF‐1α plays a synergistic role with angiotensin II in the over expression of matrix metalloproteinases 2 and 9 (MMP 2 and 9) . This is of particular interest considering that MMP 2 and 9 have been intimately implicated in the development of diastolic dysfunction …”
Section: Adipose Tissue Fibrosis and Inflammationmentioning
confidence: 99%
“…AT1R blockers were shown to suppress TGF-b1 expression in several cell types. 44,45 Sui et al 46 demonstrated that TGF-b/Smad signal pathway contributes to Ang II-mediated collagen accumulation and valsartan, a blocker of AT1R, significantly attenuates the expression of TGF-b/Smad signaling molecules; however, research results are controversial. Another study showed that ARB inhibits collagen synthesis and metabolic imbalance mediated by Ang II, but had no effect on TGF-b1-induced cardiac fibrosis and Smad signaling molecule expression.…”
Section: Discussionmentioning
confidence: 99%